Psychological and professional readiness for applying e-portfolio in the digital educational environment of universities - T. S. Putilovskaya; E. V. Zubareva; I. G. Tuchkova (Вестник университета)
The aim of the article is to look at the concept of e-portfolio for language learners, discuss the perspectives of its application in higher educational institutions of Russia and analyse the degree of readiness for introducing it in the system of education on a wide scale. Using the observations described by different researchers, training experience in teaching foreign languages and the results of interviewing students and University professors and tutors the authors arrive at a conclusion that the educational community is generally prepared for e-portfolio application. Most difficulties are related to the absence of administrative regulation, insufficient digital competency and other reasons of psychological origin which make the university staff and the students prejudiced against this highly efficient digital tool. The authors formulate a number of didactic recommendations to facilitate the introduction and effective application of e-portfolio for language learners.